RANCANG BANGUN SISTEM PELAPORAN TRANSAKSI PADA PEMBELAJARAN LABORATORIUM BANK SYARIAH DARING - Hermawan, Dadang; Mayasari, Ine; Ruhana, Nafisah (Journal of Applied Islamic Economics and Finance, 2024)
The use of the Islamic Bank Laboratory, D4 Islamic Finance Study Program must be able to carry out lectures following the demands of the industry. The practicum method requires all students to practice in finding the cause of a problem, proving the truth of a theory and concluding it. The practicum method can be carried out offline or online, which can make lectures more effective. The Islamic bank laboratory is generally used for practicum in Islamic bank application courses both manually and electronically. Existing applications have only been made up to the service product module in Islamic banks. To complete in accordance with the material taught in the electronic Islamic Banking Application course, as well as compatibility with those in the Islamic banking industry, there must be additional transaction reporting features from all fields in Islamic banks. The development of these features will improve the results of previous studies and is expected to be commercialized in the future. This research uses the Research and Development (R&D) research method with the following stages: Planning, Design, Scripting, Testing, Evaluation, and Reporting. The results showed that the transaction report feature in the electronic Islamic banking application has been made well so that it can be used by students in practicum activities.